The enigma of the lower gut-associated lymphoid tissue (GALT) - Butler, John E; Sinkora, Marek (Journal of leukocyte biology, 2013)
Artiodactyls possess GALT that appears in fetal life and is located at the extreme end of the ileum. These IPP contain mostly B cells and involute early in postnatal life. Rabbits have a similarly located lymphoid organ, called the sacculus rotundus. Studies in sheep and rabbits have led to the concept that the lower hindgut GALT represents primary lymphoid tissue for B cells and is necessary for normal B cell development, analogous to the bursa of Fabricius. This review traces the history of the observations and theories that have led to the existing concept concerning the role of lower GALT. We then review recent data from piglets with resected IPP that challenges the concept that the IPP is primary B cell lymphoid tissue and that artiodactyls and rabbits are members of the GALT group in the same context as gallinaceous birds. Eliminating the IPP as the primary lymphoid tissue for B cells leads to the hypothesis that the IPP acts as first-responder mucosal lymphoid tissue.
Keywords: savci; Antibody Formation; Apoptosis; Humans; buněčný rodokmen; druhová specificita; Chickens; střeva; imunitní systém; Germ-Free Life; Intestines; mezenterium; Models, Immunological; střevní sliznice; Immune System; lidé; zvířata; Mammals; Cell Lineage; lymfoidní tkáň; B-lymfocyty; lymphogenesis; mucosal immunity; apoptóza; bursa Fabricii; Swine; Peyer's patches; Lymph Nodes; kur domácí; B lymphocytes; lymfatické uzliny; Bursa of Fabricius; Mesentery; Lymphoid Tissue; Rabbits; B-Lymphocytes; modely imunologické; tvorba protilátek; gnotobiologické modely; Species Specificity; králíci; Animals; B cell development; Intestinal Mucosa; Peyer's Patches; Lymphopoiesis; prasata; lymfopoéza; Peyerovy pláty; Artiodactyla